Fresno County Young Lawyers Association 7th Annual Justice George Hopper Memorial Luncheon - Watkins, Howard::::::::: (1988)
Fresno County Young Lawyers Association President Brad Hill presenting the Association's 1st Annual Hon. Blaine Pettitt Mentor Award to Judge Blaine Pettitt